The Effect of Self-Efficacy, Seriousness Level of Violation, Professional Commitment, and Self-Awareness on Whistleblowing Intention - Yulia Fitri (Journal of Accounting Research, Organization and Economics, 2022)
This study aims to analyze the effect of Self-Efficacy, Seriousness Level of Violation, Professional Commitment, and Self-Awareness on the Intention of Whistleblowing at Bank Syariah Indonesia in Banda Aceh City. This study uses research subjects, namely employees at Bank Syariah Indonesia in Banda Aceh City, such as Regional Head Offices, Branch Offices, and Sub-Branch Offices. The hypothesis was tested on 80 respondents who were selected using the purposive sampling method. The data used are primary data with a questionnaire technique distributed directly to every BSI office in Banda Aceh City. The analytical method used is in the form of multiple linear regression served through SPSS 22. The hypothesis was carried out by partially and simultaneously testing with the following results: (1) Self-efficacy has no effect on Intention of Whistleblowing, (2) Seriousness Level of Violation has a positive effect on Intention of Whistleblowing, (3) Professional Commitment has a negative effect on the Intention of Whistleblowing, (4) Self Awareness has a negative effect on Intention of Whistleblowing, and (5) Self Efficacy, Seriousness Level of Violation, Professional Commitment, and Self Awareness simultaneously affect the Intention of Whistleblowing.